Pengaruh Electronic Word of Mouth dan Customer Trust terhadap Keputusan Pembelian Air Minum Kemasan Merek Aqua di Kota Demak dengan Minat Beli Sebagai Variabel Intervening - Nur Putriati; Rauly Sijabat; Noni Setyorini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Competition in the beverage packaging industry is getting tighter, requiring companies to continue to build consumer loyalty. The AQUA brand, although widely known, has experienced a decline in the Top Brand Index over the past four years, indicating a decline in consumer purchasing decisions. This study aims to examine the influence of electronic word of mouth and customer trust on purchasing decisions for Aqua brand bottled drinking water in Demak City with purchase interest as an intervening variable. This study uses a quantitative approach with a survey method and data collection through questionnaires. Data analysis techniques are carried out using AMOS-based Structural Equation Modeling (SEM). The results of the study indicate that Electronic Word Of Mouth (EWOM) does not have a significant influence on Purchasing Decisions, Customer Trust has a positive and significant influence on Purchasing Decisions, Purchase Interest has a significant influence on Purchasing Decisions, Electronic Word Of Mouth (EWOM) does not have a significant influence on Purchase Interest, Customer Trust has a significant positive influence on Purchase Interest, Electronic Word Of Mouth (EWOM) does not have a significant influence on Purchase Decisions through Purchase Interest, and Customer Trust has a significant positive influence on Purchase Decisions through Purchase Interest.